2017
DOI: 10.1111/jvim.15029
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Intravenous Administration of Cobalt Chloride to Horses on Clinical and Hemodynamic Variables

Abstract: BackgroundCobalt chloride (CoCl2) is administered to racehorses to enhance performance. The purpose of this study was to evaluate the clinical, cardiovascular, and endocrine effects of parenterally administered CoCl2.ObjectivesTo describe the effects of weekly intravenous doses of CoCl2 on Standardbred horses.AnimalsFive, healthy Standardbred mares.MethodsProspective, randomized, experimental dose‐escalation pilot. Five Standardbred mares were assigned to receive 1 of 5 doses of CoCl2 (4, 2, 1, 0.5, or 0.25 mg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 20 publications
1
10
0
Order By: Relevance
“…In our six study horses, we have demonstrated that after regular cobalt dosing over 7 weeks, no change in haematocrit was observed. This finding was consistent with that of Knych et al and Burns et al, bringing into question the validity of the proposed ‘performance enhancing effect’ of cobalt salts, namely stimulation of erythropoiesis.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In our six study horses, we have demonstrated that after regular cobalt dosing over 7 weeks, no change in haematocrit was observed. This finding was consistent with that of Knych et al and Burns et al, bringing into question the validity of the proposed ‘performance enhancing effect’ of cobalt salts, namely stimulation of erythropoiesis.…”
Section: Discussionsupporting
confidence: 90%
“…By applying a statistical process to calculate the predicted measurement rather than plotting raw data, a smoothed line is generated while maintaining the same error bars to provide a graphical representation of the measurements in an easy to interpret format (Figures ). The sample size used in this study was sufficient to demonstrate the cumulative nature of cobalt and compared favourably with sample numbers used in other studies in this area …”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Moreover, a recent study demonstrated direct adverse effects of cobalt injections on cardiovascular system in horses. In particular, it has been revealed that Co infusion resulted in tachycardia, hypertension, muscle tremors, as well as elevation of Adrenocorticotropic hormone, cortisol, and troponin I levels (Burns et al, 2017), that may subsequently result in cardiac arrest and death (Mobasheri and Proudman, 2015).…”
Section: The Use Of Cobalt In Equine Sports and Its Limitationsmentioning
confidence: 99%
“…A single IV dose of 49 mg of Co (Knych et al, 2015) achieved Co plasma concentrations in excess of 300 μg/l for only a few hours. Chronic dosing of about 1000 mg of Co (Burns et al, 2018) increased plasma Co concentrations above 300 μg/l for 50 days, and chronic dosing over 35 days with doses that failed to achieve the 300 ng/ml level (Wenzel et al, 2019) have also been performed. None of these studies demonstrated any effect on red blood cell parameters in the experimental horses, and none of these studies investigated effects of Co on exercise.…”
Section: Introductionmentioning
confidence: 99%